2020
DOI: 10.21273/hortsci15241-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diffuse Light on Microclimate of Solar Greenhouse, and Photosynthesis and Yield of Greenhouse-grown Tomatoes

Abstract: The application of diffuse light can potentially improve the homogeneity of light distribution and other microclimatic factors such as temperature inside greenhouses. In this study, diffuse light plastic films with different degrees of light diffuseness (20% and 29%) were used as the south roof cover of Chinese solar greenhouses to investigate the spatial distribution of microclimatic factors and their impacts on the growth and yield of tomato. The horizontal and vertical photosynthetic photon flux density (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Increased temperature and drought may also drive more agriculture into greenhouse settings, where different glazings can be employed to control the quantity and quality of radiation. Open-air, diffuse light greenhouses have the potential to reduce the energy demand for crop growth (Hemming et al 2008; Zheng et al 2020). We observed that diffuse light has the ability to lower leaf and greenhouse temperatures while maintaining similar light quantity, which would decrease the amount of energy spent on cooling (Elings et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Increased temperature and drought may also drive more agriculture into greenhouse settings, where different glazings can be employed to control the quantity and quality of radiation. Open-air, diffuse light greenhouses have the potential to reduce the energy demand for crop growth (Hemming et al 2008; Zheng et al 2020). We observed that diffuse light has the ability to lower leaf and greenhouse temperatures while maintaining similar light quantity, which would decrease the amount of energy spent on cooling (Elings et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are several other benefits of growing crops under covers. For instance, blueberry production is increased under covers due to early bud development [ 65 ], higher temperatures under tunnels enhance fruit setting [ 66 ], and diffusion of light favours leaf stomatal conductance and enhances photosynthesis [ 65 , 66 , 67 ]. In addition, higher productivity for the retail market is achieved by extending the growing seasons under crop covers [ 68 ].…”
Section: Blueberry Production Systemsmentioning
confidence: 99%
“…The radiance of the lighting roof and the transparency of the plastic film are the dominant factors that determine the performance of greenhouse light absorption and resulting energy performance. Previous studies on the optical properties of the lighting roof have achieved remarkable outcomes and recommended that the diffuse light plastic films can improve the homogeneity of the canopy light distribution and increase crop production [14,36]. However, only a few studies have investigated the effect of greenhouse orientation on light interception [16].…”
Section: Interception Of Solar Energy On Lighting Roof Of Csg With Di...mentioning
confidence: 99%